2015
DOI: 10.1021/acs.jpca.5b03625
|View full text |Cite
|
Sign up to set email alerts
|

Radical Pathways for the Prebiotic Formation of Pyrimidine Bases from Formamide

Abstract: The prebiotic formation of nucleobases, the building blocks of RNA/DNA, is of current interest. Highly reactive radical species present in the atmosphere under irradiation have been suggested to be involved in the prebiotic synthesis of nucleobases from formamide (FM). We studied several free radical reaction pathways for the synthesis of pyrimidine bases (cytosine, uracil, and thymine) from FM under cold conditions. These pathways are theoretically determined using density functional theory (DFT) computations… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
36
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 35 publications
(42 citation statements)
references
References 41 publications
5
36
1
Order By: Relevance
“…In contrast to the cyanoacetaldehyde based pathways proposed in the present work, previous studies have suggested competing radical based pathways using precursors such as acetylene and urea, formamide and HCN or acetylene, and 1,2‐diaminomaleonitrile . The highest barriers for the cytosine formation reported in these studies at the same theoretical level lie in the range of 24 to 40 kcal mol −1 , which is greater than the highest barrier of 16 kcal mol −1 observed in our study.…”
Section: Results and Discusioncontrasting
confidence: 88%
See 3 more Smart Citations
“…In contrast to the cyanoacetaldehyde based pathways proposed in the present work, previous studies have suggested competing radical based pathways using precursors such as acetylene and urea, formamide and HCN or acetylene, and 1,2‐diaminomaleonitrile . The highest barriers for the cytosine formation reported in these studies at the same theoretical level lie in the range of 24 to 40 kcal mol −1 , which is greater than the highest barrier of 16 kcal mol −1 observed in our study.…”
Section: Results and Discusioncontrasting
confidence: 88%
“…The selection of •NH 2 /NH 3 assisted pathways over other competing pathways reiterates the importance of •NH 2 /NH 3 pair in making prebiotic routes to formation of pyrimidines feasible by providing lower barriers. This, in turn, signposts the catalytic role of the •NH 2 /NH 3 pair, which has been previously highlighted in the formamide based mechanism for pyrimidines formation …”
Section: Results and Discusionsupporting
confidence: 61%
See 2 more Smart Citations
“…LA-VaPI was used to monitor natural and alternative nucleobase products formed in formamide and pyrazine model prebiotic reactions. The synthetic pathways postulated for the formamide reaction have been reviewed in the literature [48,50,51], and the reaction pathway for the predicted pyrazine products is outlined by Scheme 1 in supporting information. Basic sample preparation involved collecting portions of the crude product or fractions of the desalted mixture (see the Experimental section for details), followed by resuspension in DI water and filtration to remove large particulates prior to laser ablation from the sample ampoule.…”
Section: Application Of La-vapi To Reaction Product Screeningmentioning
confidence: 99%